Media Discourse Analysis on Religious Tolerance Issues in Indonesia - Maulana Hayatullah; Mohammad Ikhsan; Sasi Sabila Musakinah Ramadhany; Ilham Nur Rohman; Taufiq Hidayat (Jurnal Pelita Raya, 2025)
This study aims to open a new space for more reflective and transformative dialogue on the strategic role of the media in building an Indonesian society that is truly inclusive, just, and respectful of religious diversity. This study uses a critical qualitative approach by applying critical discourse analysis as the main framework for analysing the construction of religious tolerance discourse in the Indonesian media. By examining news, opinions, and visualisations produced by mainstream and digital media, this study adopts Norman Fairclough's model, which analyses three dimensions: text, discursive practice, and social practice. The results indicate that mainstream media are often not neutral and tend to reproduce the political or economic interests of dominant groups, so that narratives of tolerance usually only serve to legitimise false harmony. At the same time, discrimination and injustice against minorities continue. Therefore, the media must undergo a critical transformation by prioritising ethical courage, public literacy, and commitment to human rights to truly become a space for advocacy, reflection, and facilitation of change toward a more just, pluralistic, and inclusive Indonesian society.